Tot profijt van de stad. Informele politieke particpatie en geschenken in de heerlijkheid Diest (1499-1568) - Adriaens, Miet; Cools, Hans (TSEG - The Low Countries Journal of Social and Economic History, 2016)
Previous generations of researchers have suggested that seigniorial towns in the Burgundian-Habsburg Netherlands were exempted from investing in gifts to nobles and princely officers who could influence the regional and central decision process to the benefit of the town. Clearly, seignioral lords felt a natural duty to protect the needs of their towns. However, this assumption has not been tested yet. In this article we assess the network of powerbrokers that the town of Diest constructed and the position its highborn lords had in that network during the first half of the sixteenth century. We argue that conflicting interests and rivaling clients forced the town of Diest to invest in a privileged relationship with its lord. In addition, the town magistrates maintained relations with alternative power brokers.